The Effect of Watching “Marriage Is Scary” Content on TikTok on Marital Attitudes among Early Adults - Azzahra, Tazkiya; Mardianto, Mardianto (Darul Yasin Al Sys, 2026)
The rise of “marriage is scary” content on TikTok has created a digital phenomenon in which marriage is represented through negative narratives, including infidelity, domestic conflict, financial pressure, and fear of choosing the wrong partner. Such content may shape beliefs, evaluations, and perceptions of marriage among early adults, particularly those who have never been married. This study aims to examine the effect of watching “marriage is scary” content on TikTok on marital attitudes among early adults. A quantitative approach with an explanatory design was employed, involving 112 respondents selected through purposive sampling. The respondents were 18–25 years old, unmarried, active TikTok users, and had watched “marriage is scary” content on TikTok. Data were collected using a questionnaire consisting of a watching behavior scale and a marital attitude scale, then analyzed using simple linear regression with SPSS version 27. The findings indicate that watching “marriage is scary” content has a significant negative effect on marital attitudes, with a contribution of 17.7%. This result shows that the higher the tendency to watch “marriage is scary” content, the lower the individual’s positive attitude toward marriage. The study contributes to social psychology and digital media studies by demonstrating how exposure to negative marriage-related content can shape marital attitudes in early adulthood. Practically, the findings highlight the importance of digital literacy and balanced premarital education to help early adults critically evaluate marriage-related content on social media.